Design of Cryogenic Heat Exchangers and associated Sub-Systems for Controlled Cool-down and Testing of Superconducting Magnets at FRIB. Issue 1 (1st May 2022) - Hasan, N.; Ganni, V.; Fila, A.; Casagrande, F.
Abstract: The Facility for Rare Isotope Beams (FRIB) is a continuous wave heavy ion beam linear accelerator designed for a maximum beam energy of 400 kW and using in-flight (fragment) production and separation to generate rare isotope beams. Spatial separation of the isotopes is achieved by using superconducting magnets with a high magnetic field, large aperture, and iron-dominated core. There are a total of 14 superconducting magnets used in the fragment separator section of the facility. Designs for these magnets are relatively new, and it poses challenges in several aspects of the cryogenic design and operation such as, compact coil and cryostat design, thermal shield design, and a controlled cool-down to the operating temperature while avoiding high thermal stresses. Helically coiled finned-tube cryogenic heat exchanger designs are considered for the controlled cool-down of superconducting magnets with up to 22.4 tonnes of cold mass. These heat exchangers use liquid nitrogen cooled helium gas to cool the superconducting magnets. They demonstrate high thermal effectiveness and mechanical flexibility that are essential for the variable operating temperatures (300 – 80 K) experienced during a cool-down process. This paper presents an overview of the process design, analysis, fabrication and operation of cool-down heat exchangers and their associated sub-systems developed at FRIB.